Schematic structural analysis of newspaper editorials: a comparative study of the New York Times and the New Straits Times - Zarza, Sahar; Tan, Helen; Chan, Swee Heng; Mohamad Ali, Afida (Universiti Putra Malaysia Press, 2015)
This study compares the rhetorical characteristics of editorials of two different newspapers: The New York Times (NYT) and the New Straits Times (NST) in terms of the functions and occurrences of their rhetorical moves and steps. To realise the objectives, 240 selected editorials (NYT: n=120; NST: n=120) were subjected to content analysis. The analysis was conducted based on a composite framework of Bhatia's (1993), Gunesekar's (1989), Ansary and Babaii's (2005), and So's (2005) models. The analysis showed a typical rhetorical structure for editorials that includes obligatory and optional moves and steps. Variations in the use of the moves and their steps were also observed in both newspapers. Additionally, based on the functions of the moves, it was found that NYT and NST editorials have differing writing stances. To conclude, findings of this study may heighten the awareness of ESP learners on the importance of using appropriate rhetorical moves in achieving a persuasive stance in the writing of editorials. Furthermore, the results of the study may also be an invaluable resource for ESP instructors to tap into for their teaching of successful editorial writing.